2018
DOI: 10.1016/j.neuroscience.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Reductions in the Population of GABAergic Interneurons in the Mouse Hippocampus following Developmental Ethanol Exposure

Abstract: Developmental exposure to ethanol leads to a constellation of cognitive and behavioral abnormalities known as Fetal Alcohol Spectrum Disorders (FASDs). Many cell types throughout the central nervous system are negatively impacted by gestational alcohol exposure, including inhibitory, GABAergic interneurons. Little evidence exists, however, describing the long-term impact of fetal alcohol exposure on survival of interneurons within the hippocampal formation, which is critical for learning and memory processes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 85 publications
5
33
0
Order By: Relevance
“…Bird et al 13 demonstrated that ethanol vapor exposure during P2-9 (peak BEC = 221 mg/dl) reduces IN numbers in the adult mouse hippocampus; this study also found that a single vapor chamber exposure at P7 (peak BEC = 297 mg/dl) increases the number of INs that express activated caspase-3, suggesting that they are programmed to undergo apoptotic neurodegeneration. Ethanol administration to P7 mice (subcutaneous injection; peak BEC near 500 mg/dl) has been shown to reduce the numbers of PV-INs in the frontal cortex at P82 14 , as well as in the hippocampal formation (at P14 and P90-100) and the pyriform cortex (at P100) 15,16 .…”
Section: Introductionsupporting
confidence: 75%
“…Bird et al 13 demonstrated that ethanol vapor exposure during P2-9 (peak BEC = 221 mg/dl) reduces IN numbers in the adult mouse hippocampus; this study also found that a single vapor chamber exposure at P7 (peak BEC = 297 mg/dl) increases the number of INs that express activated caspase-3, suggesting that they are programmed to undergo apoptotic neurodegeneration. Ethanol administration to P7 mice (subcutaneous injection; peak BEC near 500 mg/dl) has been shown to reduce the numbers of PV-INs in the frontal cortex at P82 14 , as well as in the hippocampal formation (at P14 and P90-100) and the pyriform cortex (at P100) 15,16 .…”
Section: Introductionsupporting
confidence: 75%
“…When a binge drinking pattern of alcohol consumption is used on pregnant rats or newborn pups, there is a reduction in the cell density and number in the CA1, CA3, and DG regions only when alcohol is administered in the period equivalent to the last trimester in humans (P4 to P9 in rats) or all three trimesters (E1 to P9; Livy et al, 2003), and there are no significant effects on the cell number when alcohol is administered to the rats in the period equivalent to the first two trimesters (Maier and West, 2001), suggesting that the third trimester equivalent is the developmental period when the hippocampus is more susceptible to the effects of alcohol. Moreover, ethanol exposure during this developmental stage reduces the number of GABAergic interneurons in adulthood (P90), possibly contributing to cognitive impairment (Bird et al, 2018). Binge-like alcohol administration during the gestation period produces neurodegeneration through an apoptotic mechanism (Ikonomidou et al, 2000), which has also been observed by assessing neuronal death in rat primary hippocampal neurons obtained from fetuses exposed to alcohol during the gestation period (Akbar et al, 2006).…”
Section: Hippocampal Effects Of Alcohol In Prenatal and Neonatal Devementioning
confidence: 99%
“…EtOH is known to directly impact inhibitory cells in the brain; however, only a few studies have examined the impact of perinatal EtOH exposure on these cells in the dentate gyrus (see Table 4). In one study, a transgenic mouse model (Venus‐VGAT) was used that allowed them to directly visualize inhibitory (GABAergic) interneurons (Bird et al, 2018). This paper found a decrease in the number of interneurons in the granule cell layer (GCL) of the dentate gyrus.…”
Section: Resultsmentioning
confidence: 99%